The Role of Nutritional Counseling in Reducing the Incidence of Anemia among Pregnant Women with Iron Deficiency - Caramelia Caramelia; Anggi Vega; Yulia Ningsih (Institute of Accounting Research and Novation (IARN), 2026)
Anemia during pregnancy is a common nutritional problem that can negatively affect maternal and fetal health, primarily caused by iron deficiency and inadequate nutritional intake. This condition can increase the risk of complications such as fatigue, infection, premature birth, and low birth weight. Therefore, effective interventions are needed to improve maternal nutrition and prevent anemia during pregnancy. This study aimed to analyze the role of nutritional counseling in reducing the incidence of anemia among pregnant women with iron deficiency. The research used a quantitative approach with a quasi-experimental pretest–posttest design involving 30 pregnant women diagnosed with iron deficiency, selected using purposive sampling. Data were collected through questionnaires to assess maternal nutritional knowledge, 24-hour dietary recall to evaluate iron intake, and hemoglobin measurements to determine anemia status. The intervention consisted of structured nutritional counseling sessions conducted during antenatal care visits. Data analysis was performed using descriptive statistics and paired t-tests to compare hemoglobin levels and knowledge scores before and after the intervention. The results showed that nutritional counseling significantly improved pregnant women’s knowledge regarding iron nutrition and anemia prevention, encouraged healthier dietary behavior, and increased the consumption of iron-rich foods and adherence to iron supplementation. In conclusion, nutritional counseling is an effective strategy to improve maternal nutritional knowledge, dietary practices, and hemoglobin levels, and its integration into routine antenatal care services can contribute to the prevention of anemia and the improvement of maternal and fetal health outcomes.